Comparison Of Judicial Review: A Critical Approach To The Model In Several Countries - Wijaya, Ahmad; Nasran, Nasran (JURNAL LEGALITAS, 2021)
AbstractThe purpose of this study is to analyze the comparative model of judicial review in Indonesia and other countries. This research uses normative legal research. The approaches used by researchers in compiling this research are, among others: the legal approach; historical approach; and comparative approach. The results of this study indicate that in principle the constitutional review system in several countries shows a variety of color gradations that are tailored to the needs of each country. In general, there are 3 (three) constitutionality testing mechanisms that have been developed to date, namely: First, the constitutionality testing of laws is carried out by existing judicial institutions or non-special adjudication, namely the Supreme Court. The country that adopts this system is the United States of America. Second, the constitutionality test of the law is carried out by a special judicial institution, namely the Constitutional Court. Countries that have adopted this system are Indonesia, Germany, South Korea, South Africa, Russia, Thailand and Turkey. The constitutionality of the law is examined by non-judicial institutions. The country that adopted this system is France.